2018
DOI: 10.1007/s11056-018-9660-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of four repellents on bank vole consumption and germination of beech nuts and acorns

Abstract: Consumption and removal of buried seeds by granivorous rodents is one of the major problems when direct seeding is applied for restoration of oak (Quercus robur) and European beech (Fagus sylvatica) forests. In this laboratory study, the use of four seed treatments to potentially reduce bank vole (Myodes glareolus) consumption of beech nuts and acorns and a control was evaluated using a no-choice feeding setup. The five seed treatments were: Chili (Capsicum chinense)/coconut fat, citronella (Cymbopogon winteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
1
1
0
1
Order By: Relevance
“…These methods have been efficient in other plantation experiments, e.g. those reported by Löf et al (2019) and Villalobos et al (2019). The number of damaged plants in this research was similar to those reported in other experiments at similar latitudes.…”
Section: Effectiveness Of Indirect Control Methodssupporting
confidence: 89%
“…These methods have been efficient in other plantation experiments, e.g. those reported by Löf et al (2019) and Villalobos et al (2019). The number of damaged plants in this research was similar to those reported in other experiments at similar latitudes.…”
Section: Effectiveness Of Indirect Control Methodssupporting
confidence: 89%
“…It is well known that granivorous rodents are a major threat to successful regeneration of broadleaves. To help identify control mechanisms, Villalobos et al (2019) demonstrated that repellents may help to reduce predation of oak acorns and beech nuts by voles. Meta-analyses provide an important tool to identify generalized trends across research studies globally.…”
Section: Brief Presentation Of Special Issue Contentmentioning
confidence: 99%
“…Znaczenie aplikacyjne badań nad behawiorem antydrapieżniczym Badania reakcji zwierząt na sygnały pochodzące od drapieżników były podejmowane przez wielu autorów i dotyczą głównie ekspozycji na bodźce zapachowe (1,6,7,21,23,53,65,67,71,79,82) oraz w zdecydowanie mniejszym zakresie wizualne (39,53,57) i dźwiękowe (46,57). Obserwuje się przede wszystkim wzrost czujności oraz spadek aktywności pokarmowej i lokomotorycznej badanych osobników.…”
Section: Trwałość Behawioru Antydrapieżniczegounclassified